Inflammatory myofibroblastic tumor of the bladder in an adolescent: Case report - Linda Guan; Azeem Khan; Amy Zhou; Hubert S. Swana (Urology Case Reports, 2024)
Inflammatory myofibroblastic tumors of the bladder (IMTB) are rare neoplasms that can occur in children. These tumors have uncertain malignant potential and can present similarly to bladder sarcomas. It is important to differentiate between IMTB and bladder sarcomas using a careful immunohistochemical approach. We report a case of IMTB in a 12-year-old girl who presented with presyncope and gross hematuria. IMTB was diagnosed through immunohistochemical analysis, and clinical improvement was observed after resection of the tumor.